2019
DOI: 10.2196/preprints.16984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of MyDiabetesPlan, a Web-Based Patient Decision Aid on Decisional Conflict, Diabetes Distress, Quality of Life, and Chronic Illness Care in Patients With Diabetes: Cluster Randomized Controlled Trial (Preprint)

Abstract: BACKGROUND Person-centred care is critical to delivering high quality diabetes care. Shared decision-making is central to person-centred care, and in diabetes care, improved decision quality, patient knowledge and patient risk perception. Delivering person-centred care can be facilitated with the use of patient decision aids. We developed MyDiabetesPlan, an interactive shared decision-making and goal-setting patient decision aid designed to help individualize care priorities and to supp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Findings from this review suggest interventions that include a goal or need setting component with either a nurse (Dobke et al, 2008) or decision navigator (McBride et al, 2016) ahead of clinical consultations should assist the transfer and exchange of knowledge between patient and clinician, and lower short term decisional conflict. This finding is similar to other studies in non-wound care populations that identified goal setting decision aids reduced decisional conflicts (Yu et al, 2020). However, findings evaluating a wide range of shared decision making interventions on decisional conflict compared to usual care indicated there was little or no difference between control and intervention groups (Légaré et al, 2018).…”
supporting
confidence: 87%
“…Findings from this review suggest interventions that include a goal or need setting component with either a nurse (Dobke et al, 2008) or decision navigator (McBride et al, 2016) ahead of clinical consultations should assist the transfer and exchange of knowledge between patient and clinician, and lower short term decisional conflict. This finding is similar to other studies in non-wound care populations that identified goal setting decision aids reduced decisional conflicts (Yu et al, 2020). However, findings evaluating a wide range of shared decision making interventions on decisional conflict compared to usual care indicated there was little or no difference between control and intervention groups (Légaré et al, 2018).…”
supporting
confidence: 87%